(untitled) (Research, Society and Development, 2023)
Resin tapping is an activity that aims to extract resin from trees, and thus use this product industrially. The species most used for resin tapping in Brazil is Pinus elliottii var, elliottii. The extracted resin is basically composed of rosin and turpentine, which are used by the chemical industry. Although the main resin processes currently used are well known, new systems must be tested, such as the closed system and new compositions of stimulating pastes. These new processes and the new compositions of stimulating pastes can make the resin tapping even more efficient and profitable. Therefore, our goal was to evaluate the effect on resin production with different compositions of stimulant pastes in resin extraction, in a closed "borehole" resin system, at different collection times, in trees from a population of 10-year-old Pinus elliottii var. elliottii planted in Itapetininga, São Paulo. According to results, the effect of stimulating paste 4 (30% jasmonate, 4% naturoil and water) and paste 6 (30% jasmonate, 4% adhesive spreader and water) was evident in the highest production average resin per tree. Resin tapping in a closed process can be a good alternative for producers to better control the resin production system. The development of the chemical industry that uses products derived from resin and the growth of different markets, with considerable social, economic and environmental impacts, depends on future research and generation of technology for the production of resin and its derivatives.